A Data Base System to Analyze the Epidemiology of Chlamydia Trachomatis Infections - Fichtner, Ronald R. (1985)
Infections due to Chlamydia trachomatis and their sequelae pose a major public health problem. An estimated three to four million Americans acquire chlamydial infections each year, and thus are victimized by the most common, and possibly the most costly to the nation's health, of all of the sexually transmitted conditions. Women of reproductive age are particularly menaced, since infection may lead to pelvic inflammatory disease, ectopic pregnancy and involuntary infertility. The Centers for Disease Control (CDC) is cooperating with several communities in studies designed to acquire a more detailed description of the epidemiology of Chlamydia trachomatis infections. These studies should advance the formulation and evaluation of community-based strategies for the control of this disease. To support three of these studies, a data entry system, utilizing commercially available data base software, was developed for implementation on personal computers. It enables systematic entry of study data from medical, patient interview, and diagnostic laboratory records, and provides for the data base linkages between records required for epidemiologic analyses. Systems of this design offer cost-effective solutions to common data management problems that are shared by many public health-based programs that seek to study or control infectious diseases.